2022
DOI: 10.37236/10371
|View full text |Cite
|
Sign up to set email alerts
|

Pruned Inside-Out Polytopes, Combinatorial Reciprocity Theorems and Generalized Permutahedra

Abstract: Generalized permutahedra are a class of polytopes with many interesting combinatorial subclasses. We introduce pruned inside-out polytopes, a generalization of inside-out polytopes introduced by Beck-Zaslavsky (2006), which have many applications such as recovering the famous reciprocity result for graph colorings by Stanley. We show (quasi-)polynomiality and reciprocity results for the integer point count of pruned inside-out polytopes by applying classical Ehrhart polynomials and Ehrhart-Macdonald reciprocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Again, this definition does not change if we require the orientations h to be acyclic. A proof of these facts is implicit in previous works [BBM19] and spelled out by Rehberg [Reh21] (Proposition 3.9).…”
Section: Hypergraphic Polytopesmentioning
confidence: 62%
See 2 more Smart Citations
“…Again, this definition does not change if we require the orientations h to be acyclic. A proof of these facts is implicit in previous works [BBM19] and spelled out by Rehberg [Reh21] (Proposition 3.9).…”
Section: Hypergraphic Polytopesmentioning
confidence: 62%
“…It can be shown that δ D is a vertex of Z(G) if and only if D is acyclic, hence the above definition remains valid if we restrict D to be an acyclic orientation of G. For a simple proof of this fact, we refer to that of a more general statement given as Proposition 3.9 in [Reh21]. The following lemma is a simple consequence of the definitions (see also the discussion in [SZ98]).…”
Section: Graphical Zonotopes the Graphical Arrangement Ofmentioning
confidence: 92%
See 1 more Smart Citation